Guiding authors to reliably use taxonomic names - Bortolus, Alejandro (2012)
It is widely known that every scientific work must be verifiable and repeatable by following the details included in the Materials and Methods section. Yet despite this, a high proportion of papers dealing with species in ecology and evolution omit the taxonomic materials and methods used to validate the names of the taxa mentioned, which is likely to have negative impacts on scientific ideas, global biodiversity, and human welfare.